Student mental health : a guide for psychiatrists, psychologists, and leaders serving in higher education - Roberts, Laura Weiss, 1960- (American Psychiatric Association Publishing, 2018)
"Student Mental Health: A Guide for Psychiatrists, Psychologists, and Leaders Serving in Higher Education was created to help psychiatrists, psychologists, and campus leaders-both students and administrators-as they work to build a university culture that supports the health, resilience, and maturation of students. Organized into four parts, the book provides an overview of university student mental health and campus culture. The chapter authors address life transitions and the university student experience, as well as the challenges of caring for university students with mental health issues. The book has positive strategies, including ways to foster mental health for distinct university student populations. The use of case studies provides an immediacy that helps the reader apply critical concepts to real- world scenarios. In addition, the editor has integrated useful adult-centered learning approaches, such as key points and discussion questions, into the rich and interesting chapters to emphasize the acquisition and retention of knowledge. Finally, the book is comprehensive, offering practical clinical guidance along with insightful perspectives on university policies, systems, and cultures. Student Mental Health is both down-to-earth and aspirational, providing evidence and best practices to ensure greater mental health on campus, while stimulating conversation about how to ensure and optimize the value of higher education through thoughtful, sophisticated approaches to student mental health"--Publisher's description.